2017
DOI: 10.1007/s12028-017-0378-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid NLRP3 is Increased After Severe Traumatic Brain Injury in Infants and Children

Abstract: Background Inflammasome-mediated neuroinflammation may cause secondary injury following traumatic brain injury (TBI) in children. The pattern recognition receptors NLRP1 and NLRP3 are essential components of their respective inflammasome complexes. We sought to investigate whether NLRP1 and/or NLRP3 abundance is altered in children with severe TBI. Methods Cerebrospinal fluid (CSF) from children (n=34) with severe TBI (Glasgow coma scale score [GCS] ≤8) who had externalized ventricular drains placed for rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 37 publications
2
72
0
Order By: Relevance
“…One study performed by Lin et al found an upregulation of NLRP3, caspase-1, IL-1β, and IL-18 protein in the surgically resected cortex of severe-TBI patients in comparison with that of epilepsy patients [71]. Another recent clinical study analyzed cerebrospinal fluid (CSF) from severe-TBI pediatric patients at four time points post-injury, ranging from < 24 h to > 72 h [72], finding that pediatric TBI patients had higher CSF levels of NLRP3 than their age-matched controls (i.e., patients without TBI who underwent a lumbar puncture to rule out CNS infection). Furthermore, a CSF NLRP3 concentration > 6.63 ng/ml at any time point was associated with poorer neurological outcome as determined by the Glasgow Outcome Scale at 6 months post-TBI.…”
Section: The Nlrp3 Inflammasome and Tbi Moderate And Severe Tbimentioning
confidence: 99%
“…One study performed by Lin et al found an upregulation of NLRP3, caspase-1, IL-1β, and IL-18 protein in the surgically resected cortex of severe-TBI patients in comparison with that of epilepsy patients [71]. Another recent clinical study analyzed cerebrospinal fluid (CSF) from severe-TBI pediatric patients at four time points post-injury, ranging from < 24 h to > 72 h [72], finding that pediatric TBI patients had higher CSF levels of NLRP3 than their age-matched controls (i.e., patients without TBI who underwent a lumbar puncture to rule out CNS infection). Furthermore, a CSF NLRP3 concentration > 6.63 ng/ml at any time point was associated with poorer neurological outcome as determined by the Glasgow Outcome Scale at 6 months post-TBI.…”
Section: The Nlrp3 Inflammasome and Tbi Moderate And Severe Tbimentioning
confidence: 99%
“…15,16 Such an implication might approach high significance when NLRP3 has been proposed as a biomarker in cerebrospinal fluid in TBI patients with poor prognosis. 17 Despite all these emerging backgrounds, little has been examined in application of NLRP3 inhibitors in TBI. Applying general neuroprotectives like omega-3 fatty acids or telmisartan in experimental TBI, there are some earlier studies to suggest the association with NLRP3 inhibition may account for the therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…15 In children, the potential for a dysregulated immune response after TBI to the immature brain has been reported, and as such, evaluation of the brain cytokine response after juvenile FPI was warranted. [25][26][27] After lateral FPI in juvenile mice, we discovered rapid elevation in proinflammatory cytokines near the injury epicenter (cortex and underlying hippocampus) as well as in areas remote from impact (brainstem; Fig. 6).…”
Section: Juvenile Lateral Fluid Percussion Injury Activates Inflammatmentioning
confidence: 98%